Integrating AI in Higher Education: Prospects, Challenges, and Strategic Approaches Among Novice University Instructors - Ryan R. Pecson (Indonesian Journal of Science, Technology and Humanities, 2025)
Artificial Intelligence (AI) is a phenomenon of the present, both transforming and disrupting the academic world, which concerns many that it may replace educators' jobs in the future. Despite its popularity, academic regulations are often lacking, leaving academic works vulnerable and at risk of being jeopardized. In that note, the study examines the integration of AI by novice university instructors in their academic careers and classes, focusing on its positive applications, associated challenges, and the strategic approaches instructors utilized. This research employs a descriptive qualitative design to explore the professional experiences of five purposively selected novice teachers from a state university in the Philippines, using semi-structured interviews. Following a stringent research protocol, data collection commenced, and the results were analyzed using thematic analysis. The findings indicate that integrating AI in higher education offers numerous benefits, such as improved teaching preparation and material quality, but also presents challenges, including accessibility issues and risks to academic integrity. To maximize AI's potential, educators are adopting strategies to ensure content reliability and enhance learning; however, further research is needed to verify these findings and establish best practices across a broader population and various settings.